Heidelberg Cyber Conflict Dataset (HD-CY.CON) - Harnisch, Sebastian; Zettl-Schabath, Kerstin; Steiger, Stefan (Universität, 2021)
The Heidelberg Cyber Conflict Dataset (HD-CY.CON) has been developed at the Institute for Political Science, Heidelberg University, under the guidance of Prof. Dr. Sebastian Harnisch. HD-CY.CON is a comprehensive dataset on malicious cyber operations, integrating categories of offline conflict research with characteristics of online conflicts. Drawing on a broad variety of news sources, technical threat research reports by IT-companies and information offered by state security agencies, HD-CY.CON (currently) comprises data on 1265 cyber incidents from 2000 - 2019. The data set includes operations by states and various non-state-actors, both as attackers and victims. While existing cyber conflict datasets focus on generic categories, such as "state or state-supported" cyber operations, the Heidelberg data set offers a more nuanced differentiation of political and technical attribution statements, including the attributing initiator and its characteristics. In addition, HD-CY.CON uses conflict categories of the Conflict Barometer by the Heidelberg Institute for International Conflict Research (HIIK), thus allowing a closer examination of interaction between between offline-, and online conflict dynamics. Cyber incidents are coded according to categories of the HD.CY-CON codebook and differentiated into three main incident types: data theft, disruption and hijacking. Moreover, they are accredited an intensity score, based on technical and socio-political indicators.
Gesehen am 22.06.2023
Keywords: Forschungsdaten; Datenbank